2012
DOI: 10.3389/fphys.2012.00302
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche Analysis from Multielectrode Ensemble Recordings in Cat, Monkey, and Human Cerebral Cortex during Wakefulness and Sleep

Abstract: Self-organized critical states are found in many natural systems, from earthquakes to forest fires, they have also been observed in neural systems, particularly, in neuronal cultures. However, the presence of critical states in the awake brain remains controversial. Here, we compared avalanche analyses performed on different in vivo preparations during wakefulness, slow-wave sleep, and REM sleep, using high density electrode arrays in cat motor cortex (96 electrodes), monkey motor cortex and premotor cortex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 30 publications
6
116
2
2
Order By: Relevance
“…Moreover, it was shown that power-laws naturally emerge from the random nature of the signal and the thresholding procedure used in this analysis, and moreover these power-laws may not be statistically significant [21]. Indeed, no power-law scaling could be found from unit activity, which were better fit by double-exponential distributions [24]. These analyses rather suggest that the power-law statistics of LFP peaks does not reflect scaleinvariant neural activity.…”
Section: Local Field Potentials Are Ambiguous Measures Of Criticalitymentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, it was shown that power-laws naturally emerge from the random nature of the signal and the thresholding procedure used in this analysis, and moreover these power-laws may not be statistically significant [21]. Indeed, no power-law scaling could be found from unit activity, which were better fit by double-exponential distributions [24]. These analyses rather suggest that the power-law statistics of LFP peaks does not reflect scaleinvariant neural activity.…”
Section: Local Field Potentials Are Ambiguous Measures Of Criticalitymentioning
confidence: 93%
“…It was further shown in that both in data and surrogate models, statistical significance of these power-laws of LFP peak was poor, and depended on the threshold chosen. In [24], Dehghani and collaborators have made a statistical analysis combining multielectrode in vivo recordings from the cerebral cortex of cat, monkey and human, and did not confirm the presence of power-laws. The data rather showed an optimal fit with two independent exponential processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro experiments (small scale: Beggs and Plenz, 2003;Shew et al, 2009Shew et al, , 2011Tetzlaff et al, 2010;Friedman et al, 2012) and brain imaging studies (large scale: Tagliazucchi et al, 2012;Haimovici et al, 2013;Yu et al, 2013) provide evidence for other aspects of criticality, including experimentally confirmed predictions of optimal information processing (Shew and Plenz, 2013). These studies suggest that the intact, awake cortex might operate at criticality to take advantage of the associated optimized processing capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [60] gives much evidence in support of this point, but also mentions the results in [62], which might seem to contradict it. However, these results are based on plots of cumulative probabilities, P (X > x).…”
Section: Information Processing Bocmentioning
confidence: 69%
“…max ), which, for finite x max , does not correspond to a straight line in a log-log plot, as assumed in [62]). There also other pieces of evidence that brains are fine-tuned to the critical point of a phase transition [60,63].…”
Section: Information Processing Bocmentioning
confidence: 99%